(3eYGde GdCUhds - (3GdTGej GdYGedj, CHh efUhQ, GHf GdTgjO GdKGfj, GHf GdTgjO GdKGfj, GdMSf Hf Rjf GdOjf Hf Ydj GdTGej GdYGedj, J (B1011(3g` (B1602(3es ((3fXQ Ydj Hf eMeO UGdM GdddGgLjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdeJYGdj aj YR LdGdg Yf eWGQM GdCagGe (B... (3aEf Chdi eG GfabJ aj JMUjdg cfhR GdCYeGQ hCWGdJ (B... (3gh GdYde HGdCMcGe GdTQYjI hGdeSGFd GdabgjIs
(3BNQgG (B:s
(3BNQgG(B: (3hCeG KGfjG adCf GdEaJGA QHeG jMJed GdJChjd hEf cGf eMJedG dg dCf GMJeGd GdJYejI Ydi eG gh GdeYdhe ef CMhGd GdCFeI Ydjge GdSdGe CbQH hGXgQ hPdc cGa aj GdJQLjM acdGe GdTjN YfOj gh GdMb(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 192s
(3GdPQjYI, L (B14: 44s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs